"Melancholic? Naturally!": Impulses for Cultural Transformation from Queer-Ecological Worldmaking, Activism, and Art in a Western Context. Issue 5 (2nd October 2020) - Mühlbacher, Judith Ezra
Abstract: Although ecological grief is a common psychic response to socioecological losses, there are no shared spaces to engage with it in Western cultures—a symptom of the problematic way they conceive Nature as external and subordinate to humans. Seeking subversive impulses for paradigmatic transformation, this research centers queer-identifying eco-activists and -artists, and their practices of queer-ecological worldmaking. Arts-based research and interviews reveal the potential of melancholic grieving to create an understanding of interdependencies with the more-than-human world, as well as communities for healing. Impulses toward a joint liberation entail the extension of empathy and agency to the more-than-human world.